2022
DOI: 10.3390/ma15217827
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Se/ZnO NPs in Enhancing the Antibacterial Activity of Resin-Based Dental Composites

Abstract: Biofilm formation in the resin-composite interface is a major challenge for resin-based dental composites. Using doped z nanoparticles (NPs) to enhance the antibacterial properties of resin composites can be an effective approach to prevent this. The present study focused on the effectiveness of Selenium-doped ZnO (Se/ZnO) NPs as an antibacterial nanofiller in resin composites and their impact on their mechanical properties. Pristine and Se/ZnO NPs were synthesized by the mechanochemical method and confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The experimental materials in this research and the composite resin with 8% bioactive glass, both of which release calcium and silicon ions, demonstrated biocompatibility and minimal cytotoxicity [ 37 ]. In addition, resin with selenium-doped ZnO nanoparticles showed biocompatibility and advanced antibacterial effect [ 38 ]. Given that resin with either bioactive glass or ZnO was proven, the restorative composite resin incorporated with hCS demonstrated biocompatibility and could be a potential dental composite resin to be used in oral.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental materials in this research and the composite resin with 8% bioactive glass, both of which release calcium and silicon ions, demonstrated biocompatibility and minimal cytotoxicity [ 37 ]. In addition, resin with selenium-doped ZnO nanoparticles showed biocompatibility and advanced antibacterial effect [ 38 ]. Given that resin with either bioactive glass or ZnO was proven, the restorative composite resin incorporated with hCS demonstrated biocompatibility and could be a potential dental composite resin to be used in oral.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth defects are a common oral disease caused by various factors, such as caries, trauma, and acid erosion. Since their introduction in the 1960s, photoactivating dental resin composites have been the most prevailing direct filling material for repairing dental defects instead of amalgams for their attractive aesthetics, excellent physicochemical properties, favorable biocompatibility, and superior convenience of operation. It has been reported that these composites currently cover more than 95% of all direct restorations on anterior teeth and 50% of those on posterior teeth . These materials are mainly composed of a methacrylate-based polymeric matrix, inorganic filler, and a small amount of photoinitiator to enable polymerization under specific light conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 It has been reported that these composites currently cover more than 95% of all direct restorations on anterior teeth and 50% of those on posterior teeth. 4 These materials are mainly composed of a methacrylate-based polymeric matrix, inorganic filler, and a small amount of photoinitiator to enable polymerization under specific light conditions. However, despite their advantages, cariogenic plaque biofilm on restorations tends to accumulate more on the surface of resin composites than on other restorative materials.…”
Section: Introductionmentioning
confidence: 99%